2021
DOI: 10.1186/s12872-021-02326-6
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-375-3p is implicated in carotid artery stenosis by promoting the cell proliferation and migration of vascular smooth muscle cells

Abstract: Background Atherosclerosis is the main cause of carotid artery stenosis (CAS) which mostly occurs in the elderly. In this paper, the expression level of miR-375-3p in asymptomatic CAS patients and its diagnostic value for asymptomatic CAS were investigated, and the effects of miR-375-3p on the cell proliferation and migration of vascular smooth muscle cells (VSMCs) was further explored. Methods 98 healthy subjects and 101 asymptomatic CAS patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Research has indicated its significant upregulation in AS models and its inhibition leads to reduced intracellular lipid accumulation ( 66 , 67 ). Conversely, miR-375-3p overexpression promotes endothelial cell proliferation, migration, and phenotypic transition, potentially promoting CAS development by targeting XIAP ( 68 ). Studies have shown that miR-375-3p inhibitors exert a protective effect against high glucose- or hypoxia-induced endothelial progenitor cell (EPC) injury, and enhance the antioxidant capacity in a myocardial fibroblast model ( 69 , 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated its significant upregulation in AS models and its inhibition leads to reduced intracellular lipid accumulation ( 66 , 67 ). Conversely, miR-375-3p overexpression promotes endothelial cell proliferation, migration, and phenotypic transition, potentially promoting CAS development by targeting XIAP ( 68 ). Studies have shown that miR-375-3p inhibitors exert a protective effect against high glucose- or hypoxia-induced endothelial progenitor cell (EPC) injury, and enhance the antioxidant capacity in a myocardial fibroblast model ( 69 , 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of miR-128-3p decreases VSMCs proliferation and migration and helps VSCMs maintain a contractile phenotype [ 46 ]. In contrast, miR-375-3p overexpression has been implicated in carotid artery stenosis by promoting VSMC proliferation and migration [ 47 ]. MiR-375-3p expression was also found to be downregulated in several neural injury models, including cerebral ischemia/reperfusion injury (I/RI) models [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal migration, extracellular matrix synthesis, and proliferation of vascular smooth muscle cells (VSMCs) contribute to the formation of atherosclerotic plaque [65]. TNF-α causes VSMC proliferation and migration through multiple pathways [66][67][68][69][70][71]. It contains upregulated expression of lncRNA HIX003209, miR-21, lncRNA CAMK2D-associated transcript-1, miR-375-3p, Raf-1/MAPK-dependent manner, and the help of matrix metalloproteinase 2.…”
Section: Tnf-α and Vascular Smooth Musclementioning
confidence: 99%